Comparative Effect of Aqueous and Methanolic Bupleuri Radix Extracts on Hepatic Uptake of High-Density Lipoprotein and Identification of the Potential Target in HFD-Fed Mice. (5th December 2019) - Tan, Zhibin; Huang, Yijia; Chen, Fenglian; Cao, Cheng; Wang, Shuling
Abstract : Our previous study found saikosaponin b2 (SSb2 ) increased high-density lipoprotein (HDL) uptake in HepG2 cells. SSb2 is only found in aqueous Bupleuri Radix extract, and it is one of the secondary saponins derived from saikosaponin d (SSd), which exists in the methanolic extract. This study aimed to compare the effect of aqueous extract of Bupleuri Radix on hepatic uptake of HDL with methanolic extract and to reveal the underlying mechanism of enhancing HDL uptake in mice fed with high-fat diet (HFD). Cellular HDL uptake in each group was quantified by flow cytometry. Bioactive components bound to the HepG2 cytomembrane were detected with HPLC-DAD. RNA sequencing was performed to screen the underlying target on hepatic HDL-uptake, and western blotting was conducted to verify differential protein expression. Significant increases of HDL uptake by HepG2 cells were observed in all groups of aqueous extract of Bupleuri Radix, while no effect or negative effect was observed in the methanolic extract. Saikosaponin b1 (SSb1 ) and SSb2 were detected in the desorption elute of the aqueous extract from the HepG2 cytomembrane, while saikosaponin a (SSa) and SSd were not found. Remarkable upregulation of FGF21 in HFD-fed mice liver was affirmed after treatment with aqueous extract. This study suggested that aqueous Bupleuri Radix extract could promote hepatic HDL uptake in vitro but methanolic extract could not, and FGF21 might be the potential target.